2010
DOI: 10.1097/ss.0b013e3181e0cbac
|View full text |Cite
|
Sign up to set email alerts
|

Palygorskite Formation Under the Influence of Saline and Alkaline Groundwater in Central Iranian Soils

Abstract: Few studies have investigated the formation or instability of palygorskite under the influence of groundwater. This study aims to identify the effects of a saline and sodic groundwater on the formation of palygorskite and the associated clay minerals. Four pedons along a calcareous catena with different depths of groundwater were sampled and analyzed using X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and inductively coupled plasma mass spectrometry. Chemical compositions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For example, saponite was recognised as an alteration product of bentonite by Cuevas (2004), secondary Mg-enriched mineral phases have been observed at the Tournemire analogue site (Tinseau et al, 2006;Techer et al, 2012) and palygorskite was identified as an Mg-rich alteration product of bentonite by high pH groundwaters in the Troodos natural analogue site (Alexander et al, 2012). The formation of these phases at these high pH conditions is not unexpected as they are commonly associated with alkaline, saline lake environments (Yeniyol, 2007(Yeniyol, , 2012Hojati et al, 2010;Akbulut and Kadir, 2003) where they form from post-sedimentary alteration of soils and rocks in high pH fluids in the presence of dolomitic material (Derkowski et al, 2013;Xie et al, 2013;Schwarzenbach et al, 2013;Birsoy, 2002). Their formation has also been identified in cement-aggregate systems where dedolomitisation in the presence of Ca(OH) 2 and amorphous silica resulted in the formation of a mixed calciummagnesium silica gel (Gali et al, 2001).…”
Section: Mg-silicate Formationmentioning
confidence: 92%
“…For example, saponite was recognised as an alteration product of bentonite by Cuevas (2004), secondary Mg-enriched mineral phases have been observed at the Tournemire analogue site (Tinseau et al, 2006;Techer et al, 2012) and palygorskite was identified as an Mg-rich alteration product of bentonite by high pH groundwaters in the Troodos natural analogue site (Alexander et al, 2012). The formation of these phases at these high pH conditions is not unexpected as they are commonly associated with alkaline, saline lake environments (Yeniyol, 2007(Yeniyol, , 2012Hojati et al, 2010;Akbulut and Kadir, 2003) where they form from post-sedimentary alteration of soils and rocks in high pH fluids in the presence of dolomitic material (Derkowski et al, 2013;Xie et al, 2013;Schwarzenbach et al, 2013;Birsoy, 2002). Their formation has also been identified in cement-aggregate systems where dedolomitisation in the presence of Ca(OH) 2 and amorphous silica resulted in the formation of a mixed calciummagnesium silica gel (Gali et al, 2001).…”
Section: Mg-silicate Formationmentioning
confidence: 92%